Patrimonio cultural inmaterial y desarrollo turístico de la parroquia San Gerardo, cantón Guano - Rómulo Javier, Satán Guerrero (2019)
The purpose of this research is to analyze the influence of intangible cultural heritage in the tourism development of San Gerardo Parish, Guano Canton. The research is descriptive and correlational, with a non-experimental cross-sectional study design, for which a survey was applied for the independent variable and other for the dependent variable. For the intangible cultural heritage variable (VI), the inhabitants between 24 and 25 years of age of the San Gerardo parish was select as a sample, taking into account: the practical components, cultural expressions and cultural knowledge, while for the tourism development variable (VD), 8 authorities of the Decentralized Autonomous Government of the San Gerardo Parish had participate, where aspects such as facilities, services and employment generation were analyzed. Once the data were obtained from the application of the surveys, we verify both the general and specific hypotheses through the use of Pearson Chi- Square statistic of that evidences the intangible cultural heritage and its components as an influential on tourism development except for cultural practices, considered as a low importance for the inhabitants. The analyzed of this components leads to a proposal aimed at generate a management model that contributes to tourism development, taking advantage of intangible cultural heritage.